(untitled) - Solomon, Michael R. (New Jersey, 2001)
This book explores the many facets of consumer behavior. Its current coverage and engaging writing style reflect the latest research and hip trends. Chapter topics look at consumers as individuals and decision-makers, income and social class, various subcultures, and cultural influences on consumer behavior. This edition expands its focus on online consumer behavior and contains new topics such as virtual communities, virtual marketing, e-commerce For individuals with an interest in the attitudes and activities of today's buyer in the marketplace.
Keywords: Consumer behavior